Improving High-Level Thinking Skills in Students Through Powtoon-Based Animation Video Media - Rahmawati, Fahni; Ramadan, Zaka Hadikusuma (Journal of Education Technology, 2021)
Students are less able to optimize higher-order thinking skills. There are still many students who are confused in working on problems related to higher thinking skills. This paper provides a template for preparing papers for electronic production of the Journal of Education Technology. A well-prepared abstract enables the reader to identify the basic content of a document quickly and accurately, to determine its relevance to their interests, and thus to decide whether to read the document in its entirety. The Abstract should be informative and completely self-explanatory, provide a clear statement of the problem, the proposed approach or solution, and point out major findings and conclusions. The Abstract should be 150 to 250 words in length. The abstract should be written in the past tense. Standard nomenclature should be used and abbreviations should be avoided. No literature should be cited. The keyword list provides the opportunity to add keywords, used by the indexing and abstracting services, in addition to those already present in the title. Judicious use of keywords may increase the ease with which interested parties can locate our article.